Political Support in Hard Times: Do People Care about National Welfare? - Jana Friedrichsen; Philipp Zahn (University of Mannheim, Department of Economics, 2012)
During the Great Recession mass demonstrations indicated weakened political support in Europe. We show that growing dissatisfaction reflects poor economic conditions; unemployment is particularly important. Using individual level data for 16 Western European countries for 1976-2010, we find that national economic performance even matters beyond personal economic outcomes. Finally, while effects of growth and unemployment rates are the same across demographic subsets, the effect of inflation is heterogeneous. Younger, well-educated, or working individuals put relatively higher weight on price stability than the elderly, less skilled or not working. Our findings reinforce the political importance of employment and growth policies.
urn:nbn:de:bsz:180-madoc-320765
Keywords: H11; O43; P16; 330; Political support; satisfaction with democracy; growth; unemployment; collectivism